Marketinški vidiki klasificiranja izdelkov - Snoj, Boris (Akademija MM, 1998)
In his article author reveals marketing perspective in the classification of products. In marketing terms products are combinations or bundles consisting of physical elements and activities giving benefits to the parties engaged in the exchange processes. The elements and activities can be either the main reason of the exchange or its facilitator or promotor. The classification of whatever objects under investigation plays the fundamental role in the development of the theory. Especially it is crucial in the development of the descriptive theory. It enables better understanding of similarities and differences among the objects of investigation. It can be also usefull to investigate the impact of the differences among products on their management. In the marketing theory there exists already long tradition of product classifications. However the majority of classification schemes are too teoretical to be usefull in real-life business decisionmaking. In its article author critically reveals several of the most often used product classification schemes in marketing. The majority of authors in marketing believe that the most usefull product classification scheme is the one according to the characteristics of customer behaviour in the buying processes. This scheme clasifies the products according to the degree of effort (money, time and energy) the customer is willing to expend to acquire a given product and the perceived risk that the product will not deliver the benefits sought. To author's oppinion, despite some obvious qualities in comparison with the other classification schemes, this scheme can only serve as a general tool that gives path to more profound analysis of particular product marketing characteristics. Its application to specific products into categories. Therefore products should be analysed on the continuum that gives only fuzzy and relative borders among specific product. It is not the fundamental characteristics of the specific product that classify it into certain category of the products but the managerial decisions about it and the customer perception of it.
Keywords: izdelki; klasifikacija; konkurenčnost; marketing; potrošniki; povpraševanje; trženje